Economic change in South-East Asia, c.1830-1980 - Brown, Ian (Ian George) 1947- (Oxford University Press, 1997)
This book provides an introduction to the economic history of South-East Asia from the early nineteenth century to the contemporary period. It examines, for example, the strong commitment of agriculturists across the region to cultivation for export markets from the middle decades of the nineteenth century, and the impact of agricultural specialization on their material welfare; the economic role of the immigrant Chinese as traders, moneylenders, revenue farmers, bankers, and industrialists; the impact of the inter-war depression on the economies of South-East Asia; the implications of the Green Revolution in rice for rural inequalities; and the causes and nature of South-East Asia's modern industrialization. On each topic, it attempts to draw the reader into the specialist literature, to emphasize divergent views, and where appropriate, to admit ignorance. Above all, it seeks to kindle curiosity and enthusiasm, to encourage the reader to explore further.